Relationship Between Vitamin D and Hormones Important for Human Fertility in Reproductive-Aged Women - Chu, Chang; Tsuprykov, Oleg; Chen, Xin; Elitok, Saban; Krämer, Bernhard K.; Hocher, Berthold (Frontiers in Endocrinology, 2021)
Vitamin D deficiency is very common in women of reproductive age. Studies in animals suggests a link between vitamin D and reproductive hormone biosynthesis. A systematic analysis of the correlation of reproductive hormones in reproductive-aged women with both total and free vitamin D was, however, not done so far. This cross-sectional study was performed in 351 healthy reproductive age Caucasian women (median age, 28.0 years; interquartile ranges, 24.7-31.0 years). We measured serum levels of both total and free 25(OH)D, endocrinological, hematological and biochemical parameters. Spearman’s rank correlations were performed to assess the correlation between 25(OH)D metabolites and selected parameters. Total vitamin D and free vitamin D measurements correlated well (rho=0.912, p < 0.0001). Both total 25(OH)D and free 25(OH)D showed significant negative correlation with FAI (rho=-0.229, p<0.0001 and rho=-0.195, p<0.0001 for total and free 25(OH)D, respectively); LH (rho=-0.177, p=0.001 and rho=-0.114, p=0.04 for total and free 25(OH)D, respectively), testosterone (rho=-0.174, p=0.001 and rho=-0.190, p<0.0001 for total and free 25(OH)D, respectively) and AMH (rho=-0.130, p=0.015 and rho=-0.107, p=0.047 for total and free 25(OH)D, respectively). Our study showed comparable correlations of both total and free 25(OH)D with endocrinological parameters, i.e. inverse correlations with free androgen index, luteinizing hormone, testosterone, LH/FSH ratio, androstenedione and anti-Müllerian hormone, and also with hematological and biochemical parameters, i.e. inverse correlations with erythrocytes, hsCRP and leukocytes count, and positive correlation with transferrin saturation, mean corpuscular hemoglobin and mean corpuscular volume in healthy reproductive age women.